Preparation and Properties of Polycrystalline and Epitaxial Manganite Films for Pulsed Magnetic Field Application - Stankevič, V.; Anisimovas, F.; Abrutis, A.; Plaušinaitienė, V.; Novickij, J.; Bartkevičius, S. (Elektronika ir Elektrotechnika, 2005)
Deposition techniques and conditions used for preparation of thin manganite films on which bases pulsed magnetic field sensors were developed are described. High quality epitaxial and polycrystalline La0.83Sr0.17MnO3 and La0.67Ca0.33MnO3 films are prepared by pulsed liquid injection MOCVD technique and laser deposition. Possibilities to obtain variation in very wide range of electrical and magnetic properties of the films changing the deposition conditions, substrates, film structure and thickness are shown. Increase in polycrystallinity and non-homogeneity of the film’s structure leads to increase in specific resistance and decrease of the maximum temperature of ρ(T) dependence. The similar behaviour could be obtained decreasing thickness of epitaxial film down to several nanometres. Magnetoresistance MR of films prepared by different techniques and at different conditions was investigated at pulsed magnetic fields up to 35 T. The obtained results showed that polycrystalline films have several advantages in comparison with epitaxial ones for the development of pulsed magnetic field sensors. In spite of lower MR sensitivity, polycrystalline films have no MR saturation effects in high magnetic fields and can be successfully used to measure absolute value of the fields up to 35 T. Ill. 8, bibl. 5 (in English; summaries in Lithuanian, English, Russian).